MIGRÂNEAS E CEFALÉIA DO TIPO TENSIONAL CRÔNICA: ABORDAGEM DIAGNÓSTICA POR MÉDICOS NÃO-NEUROLOGISTAS. - Galdino, Gilma Serra (2006)
Doctors belonging to a Medical Services Cooperative in Campina Grande were interviewed with the objective to determine their diagnostic accuracy when faced with clinical cases of primary headache, and also to appreciate the amplitude of their knowledge about headache classification and procedures concerning exams prescriptions and therapeutic indications. Methodology. The method of extensive direct observation through the application of a questionnaire was used. The doctors were presented with three fictitious clinical histories which represented situations of frequent primary migraines such as: migraine with aura (MA), migraine without aura (MO) and chronic tensional-type headache (CTTH) according to criteria established on International Headache Classification, second edition (IHCD-II), 2003, by the Headache Classification Subcommittee as part of the International Headache Society (IHS). 173 out of 462 doctors members of the Cooperative were contacted and 91 of these accepted to take part in the study. Results. In the group of 91 doctors interviewed, 51 (56%) were male, 35 (38,5%) were female and five (5,5%) refused to answer. Their age varied from 27 to 70 years old (44,8 + 09 years old). Their experience as doctors varied from three to 46 years (21,4 + 8,2 years). 67 (73.6%) stated to have been in a medical internship. The doctors interviewed were doctors of several areas. About the accuracy of the diagnostic test, concerning MO, 60 participants (66%) identified the case as migraine, only two (2,2%) identified the MO subtype and two (2,2%) suggested it was a case of mere headache. For the clinical case of MA, 25 doctors (27,5%) said it was a case of migraine and only one (1,1%) identified it as MA. About the diagnostic of CTTH, 12 doctors (13,2%) acknowledged it as tensional headache and there was not any reference to the CTTH subgroup. Among other possibilities of diagnostic, the most mentioned ones were migraine 36 (39,6%), secondary headache to systemic arterial hypertension 12 (13,2%) and headaches caused by brain expansive process 06 (6,6%). For the three clinical cases, most of the doctors researched 79 (86,8%) in the example of MO, 74 (81,3%) in the cases of MA and 71 (78%) in the example of CTTH wouldn´t prescribe complementary exams. Regarding treatment 77 (84,6%) in the case of MO, 80 (87,9%) in the case of MA and 67 (73,6%) in the case of CTTH decided not to treat it. Among those who forwarded the case to a neurologist, we have 67 (73,6%) for MO, 78 (85,7%) for MA and 59 (64,8%) for CTTH. 65 (71,4%) doctors who were interviewed said to be unaware of the IHS diagnostic criteria for primary headaches. Conclusion. Migraine was the most common initial diagnosis for any kind of headache without any identification of the subgroups. The CTTH was subdiagnosed being frequently misidentified as migraine cases despite it is the most prevailing kind of primary headache. Most of the doctors interviewed (p<0,05) does not prescribe complementary exams for headache patients and prefer to forward them to a specialist, choosing not to treat them. These results show the lack of information found in the doctors interviewed about the diagnostic criteria for the several kinds of primary headaches.